Reformasi Struktur Pemerintahan Menurut Undang-Undang Nomor 32 Tahun 2004 - Azima Dimyati (PUBLICA, 2011)
In regional autonomy laws, the government handed over the authority to the provincial government, district and city that include more space for functions and activities transferred to the local government including government administration sectors. Regional autonomy is the right, authority, and obligation of local autonomy to regulate and manage its interestâs society except the foreign affairs politic, defense, security, justice, monetary, national fiscal and religion.Decentralization will increase the ability of local government to pay attention to the right and their community, the best way out, and also to improve the acceleration of social and economy development areas. Decentralization is conducted together with the deconcentration and assisting tasks, to enhance the creativity of local government apparatus that are actively doing the planning, implementation, and supervision of all government activities including the development.The district government and the city become an appropriate level where the devolution of power and resources will be handed over according to government functions Â and activities over a wider area. They do the next five years development, following with the identification of influenced factors including the various issues and conduct the policy steps that need to be implemented in a systematic and integrated way.Reformation of government structure at the provincial, district and city gives a wide power and responsible for managing their own area. Local government should really implements the functions, rights and obligations under the regional autonomy law. The community expect the leader grading from the provincial level, district, city, sub district and village, that they must have the ability of honest, competent, responsible, moral integrity, and able to sacrifice for the benefit of society. The desire of society to achieve their future goal that is the prosperous society, expects the provincial government leaders to the existing village leaders are not doing things that deviate from practice to meet the interests of individual, group, and political party. As it is known that corruption, collusion and nepotism are increasingly and becoming unmanageable in the level of bureaucracy.